PENGABAIAN PEMBERIAN NAFKAH SUAMI PADA ISTRI SEBAGAI ALASAN PERCERAIAN MENURUT IBNU HAZM - Ahmad Nabil Atoilah; Tsamrotul Rohmah (Istinbath | Jurnal Penelitian Hukum Islam, 2018)
Marriage is a matter of essence for man, all human beings have a sexual instinct, if this is not regulated then it can become wild like an animal. Therefore Islam arranges it in detail in the Shari'ah from the tips of choosing a spouse, Islamic guidance in the wedding, and around the life of the household in order to avoid self-harm or the community. One of the things that often happens in the issue of marriage is the lack of economic or "livelihood". The problem of lack of husband's livelihood given to the wife is due to the negligence of the husband to his duty as head of the family and less effort in searching for treasure to support his wife and family. such a reality occurs mostly in societies that lack knowledge of how to obtain a right.